1998
DOI: 10.1037/1099-9809.4.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity ideology among young African American and European American women and men in different regions of the United States.

Abstract: Although both gender and race differences in masculinity ideology were significant, gender had a larger effect size. Study 2, focused on the effect of residence in different geographic regions of the country, compared the MRNI scores of the more metropolitan Northeastern and Mid-Atlantic sample of the present study with those of the more rural Southern sample used by Levant and Majors. This study found that the effect of geographic place of residence moderates the effect of race on masculinity ideology, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(116 citation statements)
references
References 17 publications
6
108
2
Order By: Relevance
“…Black men (Levant, Majors, & Kelley, 1998) and Black and Latino men (Levant et al, 2003). A consistent finding among these studies is that men and racial-ethnic minorities tend to report higher levels of TMI compared to women and individuals from the racial-ethnic majority (c.f., Levant & Richmond, 2016).…”
Section: Indeed Investigators Have Examined Different Versions Of Thsupporting
confidence: 67%
“…Black men (Levant, Majors, & Kelley, 1998) and Black and Latino men (Levant et al, 2003). A consistent finding among these studies is that men and racial-ethnic minorities tend to report higher levels of TMI compared to women and individuals from the racial-ethnic majority (c.f., Levant & Richmond, 2016).…”
Section: Indeed Investigators Have Examined Different Versions Of Thsupporting
confidence: 67%
“…American men in the south (Levant, Majors, & Kelley, 1998) and those who participated in church activities (Hunter & Sellers, 1998) were found to adhere to the traditional masculine ideology more than White men in the same setting. It appeared that, depending on where the African American men lived (i.e., rural versus urban), their endorsement of traditional masculine attitudes varied accordingly.…”
Section: Social C Lassmentioning
confidence: 99%
“…Multidimensionality suggests the need to assess support for dominant norms rather than a single masculinity or femininity script. Individual endorsement of these is seen to vary over context and time as well as across age; culture; sexual orientation; social class; and 'race' (Levant andMajors 1997, Levant andFischer 1998). In addition the assumed independence of masculinity and femininity requires that attitudes toward these constructs are assessed apart.…”
Section: The 'Gender Ideology' Approach To Measurementmentioning
confidence: 99%
“…It accounts for differential endorsement of gender norms, at an individual or group level, across dimensions. For example, empirical studies using the Male Role Norms Inventory (Levant et al, 1992) have found variable support for masculine norms along gender (Levant & Majors, 1997;Levant, Majors & Kelley, 1998;Levant et al, 1996); 'race' (Levant & Majors, 1997); and cultural lines . Findings even suggest urban-rural variation .…”
Section: The 'Gender Ideology' Approach To Measurementmentioning
confidence: 99%